High-frequency monitoring of surface water quality at the outlet of the Ibrahim River (Lebanon): A multivariate assessment. (September 2019) - El Najjar, Paula; Kassouf, Amine; Probst, Anne; Probst, Jean-Luc; Ouaini, Naim; Daou, Claude; El Azzi, Desiree
Highlights: Organic and bacteriological parameters differentiate low and high river discharges. Mineral variables show a clear annual discrimination in water trends. PCA rendered data reduction proposing only 10 parameters to assess variations in water quality. WQI calculation was applied and showed medium to good water quality. Abstract: Surface water quality monitoring is essential to evaluate the quality of a water resource. The current study assesses the quality of the Ibrahim River, one of the main Lebanese rivers, exposed to considerable human activities. 285 samples were collected at the outlet of the river, between May 2016 and July 2017, covering one hydrological year. Twenty-three physico-chemical parameters (flow, pH, temperature, electrical conductivity, turbidity, total suspended solids, total dissolved solids, dissolved oxygen, dissolved organic carbon, biochemical oxygen demand, chemical oxygen demand, chemical oxygen demand/biochemical oxygen demand, specific ultraviolet absorbance, dissolved cations (Na +, K +, Ca 2+, Mg 2+ ), total alkalinity, dissolved anions (Cl −, NO3 −, NO2 −, PO4 3− and SO4 2− )) and five microbiological tests were assessed (total germs, total coliforms, fecal coliforms, Escherichia coli and Enterococcus ). A Principal Component Analysis (PCA) was applied for data analysis. The first component showed high levels of anthropogenic characteristics mainly due to organic and bacteriological parameters, differentiating low and high river discharges (explaining around 35% of the total variance). The second component was mainly influenced by mineral variables showing a clear annual discrimination (explaining about 17% of the total variance). Moreover, this study led to variables reduction from twenty-eight to ten. The final shortlisted parameters are Q, pH, EC, NO3 −, total coliforms, fecal coliforms, BOD5, K +, TA and Cl − . A new PCA performed with the reduced matrix validated this selection. The water quality index (WQI) was then calculated in this study, using the shortlisted parameters characterizing the basin, excluding the flow since it cannot be considered as a quality indicator. Thus, the water was evaluated as « medium » to « good » with values ranging from 63.1 (August 2016) to 73.1 (November and December 2016) with an average of 69.0 ± 1.9. The proposed WQI should be further tested for monitoring practices in the Ibrahim River basin or other similar basins of the region.